Innovation and Adoption of Electronic Business Technologies - Kai Sülzle (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
This paper presents a duopoly model of e-business technology adoption. A leader and a follower benefit from a new ebusiness technology with uncertain quality depending on its innovation and adoption cost and both firms' adoption timing. When innovation and adoption require large set-up costs, the leader favors quick adoption by the follower. The follower prefers either late or no adoption. This is due to a delayed firstmover benefit which stems from an innovators' capability to impose a new technology standard. It is shown that inter-firm adoption subsidies are a viable tool to quicken adoption.
Keywords: L1; O31; 330; Electronic Business; Adoption; Innovation; Network Effects; E-Business; Informationstechnik; Innovationsdiffusion; Duopol; Network Externalities; Theorie